METODE PENGELOLAAN SAMPAH RUMAH TANGGA: SURVEY KEPERAWATAN KESEHATAN KOMUNITAS DI AREA PEDESAAN KABUPATEN PROBOLINGGO JAWA TIMUR - Roisah; Nurul Laili (STIKes Maharani Malang, 2022)
Introduction: Waste management is still a problem in the community. The results of the study found that the largest waste recycling sorting was household waste and 90.47% did not provide a place for garbage collection in the house and waste management has not been carried out properly. The main factors related to waste management are the lack of alternative waste disposal options, household attitudes, and lack of awareness. The main challenge for poor waste management from both local governments and households is that bad waste management practices require policies related to waste management. Objective: The purpose of this study was to determine the method of household waste management in rural areas of Probolinggo Regency. Methods: This research is descriptive research using a survey method with an action research approach, the population of this research is all heads of families in Sentong Village, Probolinggo Regency, sampling technique using random sampling with a sample of 777 families. The instrument used was an environmental health questionnaire in the community nursing assessment and observation format. Results and analysis: The data analysis in this study uses descriptive statistics of trends and graphics to see the pattern of people's habits in waste disposal and management. The study findings show that the community waste disposal method is mostly burned by as many as 404 families (51.9) % and waste disposal to the Got is 447 families (44.7%) and waste management is mostly indiscriminate by as many as 542 families (69.7%). Discussion: This study shows that most people have not managed household waste properly, so this study recommends the importance of facilitating proper waste management so that the community commits to implementing environmental health programs. Keywords: Waste Management, Household, Community Health